2001
DOI: 10.1038/sj.bmt.1703226
|View full text |Cite
|
Sign up to set email alerts
|

Oral eicosapentaenoic acid for complications of bone marrow transplantation

Abstract: Summary:The 'systemic inflammatory response syndrome' (SIRS) may represent the underlying cause of complications after bone marrow transplantation (BMT). This study was conducted to determine whether blocking the etiologic factors of SIRS could improve the complications of BMT. Sixteen consecutive patients with unrelated donors were allocated alternately to two groups. Seven patients received 1.8 g/day of eicosapentaenoic acid (EPA) orally from 3 weeks before to about 180 days after transplantation, while nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 22 publications
3
74
0
2
Order By: Relevance
“…Among the five nonrenal transplant studies that were found (three on heart transplantation, one on liver transplantation, and one on bone marrow transplantation), the only potentially important clinical benefit reported was a reduction in acute colonic graft versus host disease and improved survival in a small RCT in bone marrow transplantation (30,31). However, there have been no additional studies to confirm these observations, raising concern as to whether the authors or other groups may not have been able to reproduce these results.…”
Section: Discussionmentioning
confidence: 99%
“…Among the five nonrenal transplant studies that were found (three on heart transplantation, one on liver transplantation, and one on bone marrow transplantation), the only potentially important clinical benefit reported was a reduction in acute colonic graft versus host disease and improved survival in a small RCT in bone marrow transplantation (30,31). However, there have been no additional studies to confirm these observations, raising concern as to whether the authors or other groups may not have been able to reproduce these results.…”
Section: Discussionmentioning
confidence: 99%
“…64 Meta-analyses showed favourable effects of an enteral nutrition containing a high concentration of n-3 fatty acids on mortality, secondary infections and length of hospital stay in ICU patients with sepsis, acute respiratory distress syndrome and systemic inflammation response syndrome. 64 Systemic inflammation response syndrome has also been linked to the aetiology of GVHD, 65,66 and grade C evidence suggests beneficial effects of eicosapentaenoic acid: in a small prospective study, supplementation of eicosapentaenoic acid around BMT was associated with a reduction of inflammatory cytokines (IL-10, TNF-a and IFN-g), reduced vascular endothelial dysfunction, higher survival rate 67 and a lower grade of acute colonic GVHD. 68 Glutamine, arginine and nucleotides.…”
Section: Nutritional Support In Gvhd Of the Digestive Tract Bs Van Dementioning
confidence: 99%
“…64 Systemic inflammation response syndrome has also been linked to the aetiology of GVHD, 65,66 and grade C evidence suggests beneficial effects of eicosapentaenoic acid: in a small prospective study, supplementation of eicosapentaenoic acid around BMT was associated with a reduction of inflammatory cytokines (IL-10, TNF-a and IFN-g), reduced vascular endothelial dysfunction, higher survival rate 67 and a lower grade of acute colonic GVHD. 68 Glutamine, arginine and nucleotides. The nonessential amino acid glutamine is a precursor for nucleotide synthesis; rapidly dividing cells, such as enterocytes, are most likely to suffer from a shortage of glutamine.…”
Section: Nutritional Support In Gvhd Of the Digestive Tract Bs Van Dementioning
confidence: 99%
“…Omega-3 PUFA have been shown to be antiinflammatory and immunomodulatory in the attenuation of cellular injury (8)(9)(10)(11)(12)(13). Recently, there has been much interest in the use of fish oil contacting ω3PUFA to treat parenteral nutrition-associated liver disease (PNALD) in children (14).…”
mentioning
confidence: 99%